2022
DOI: 10.1158/1541-7786.mcr-21-0302
|View full text |Cite
|
Sign up to set email alerts
|

GAS6/AXL Inhibition Enhances Ovarian Cancer Sensitivity to Chemotherapy and PARP Inhibition through Increased DNA Damage and Enhanced Replication Stress

Abstract: Over 80% of women with high-grade serous ovarian cancer (HGSOC) develop tumor resistance to chemotherapy and die of their disease. There are currently no FDA-approved agents to improve sensitivity to first-line platinum- and taxane-based chemotherapy or to PARP inhibitors. Here, we tested the hypothesis that expression of growth arrest–specific 6 (GAS6), the ligand of receptor tyrosine kinase AXL, is associated with chemotherapy response and that sequestration of GAS6 with AVB-S6–500 (AVB-500) could improve tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…SND1 may promote the expression of GAS6, which may regulate the chemotherapy sensitivity of SKOV3 cells through the AKT signaling pathway. This is consistent with previous reports that GAS6 binds to the receptor Axl [27], which leads to the auto-phosphorylation of Axl and then binds to the growth factor receptor-binding protein, thereby activating the PI3K/AKT signaling pathway, enhancing the survival and invasion of cells and inhibiting apoptosis [22,28]. However, whether transcriptional activation by SND1 is the only mechanism to keep GAS6 expression within SKOV3 cells or other transcription factors or epigenetic regulation mechanisms are also involved needs further investigation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…SND1 may promote the expression of GAS6, which may regulate the chemotherapy sensitivity of SKOV3 cells through the AKT signaling pathway. This is consistent with previous reports that GAS6 binds to the receptor Axl [27], which leads to the auto-phosphorylation of Axl and then binds to the growth factor receptor-binding protein, thereby activating the PI3K/AKT signaling pathway, enhancing the survival and invasion of cells and inhibiting apoptosis [22,28]. However, whether transcriptional activation by SND1 is the only mechanism to keep GAS6 expression within SKOV3 cells or other transcription factors or epigenetic regulation mechanisms are also involved needs further investigation.…”
Section: Discussionsupporting
confidence: 93%
“…GAS6 is a secreted protein that interacts with receptor tyrosine kinases to activate downstream signaling pathways and involves some biological processes [21]. It has been reported that GAS6 can regulate the sensitivity of lung cancer to chemotherapy drugs through PI3K/AKT signaling pathway [22,23]. In the present study, we provide evidence regarding the relationship between SND1 and GAS6/AKT, which is also involved in the anti-apoptotic mechanism of SND1 protein in the cisplatin-induced apoptosis of SKOV3 ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…56 In line, a very recent study by Mullen et al on ovarian cancer demonstrated a strong sensitization to chemotherapy and Poly (ADPribose) polymerase (PARP)-inhibition through AVB-500 meditated GAS6 neutralization. 57 Furthermore, a recent study from Hirokazu et al demonstrated that tumor-associated macrophages-secreted PROS1 functions as a ligand of AXL to sustain the aggressive properties of glioma sphere cultures and that their expression is strongly correlated with poor survival outcomes for glioblastoma multiforme patients. 34 In the present story, we show that loss of AXL signaling through siRNA interference or the small molecule inhibitor Bemcentinib (R428) efficiently impaired the capacity of BLBC cells to survive conventional cytotoxic chemotherapy, thereby identifying AXL as a druggable target to sensitize cancer cells to cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In functional assays, using PDOs from ten patients that were insensitive to platinum, indicated that these PDOs were sensitive to such tyrosine kinase inhibitors as the EGFR/HER2 inhibitors, lapatinib and WZ8040, while the use of PI3K and CHEK1 inhibitors, BGT226 and CHIR-124, led to the significant inhibition of tumor progression [ 127 ]. In another study using PDOs from a chemoresistant patient, treatment with AXL inhibitor AVB500 resulted in limited tumor survival when used in combination with olaparib, independently of the HR status of the tumor [ 130 ]. In addition, the inhibitor had a synergistic DNA-damaging effect with carboplatin and paclitaxel treatment, suggesting that AVB500 treatment could be beneficial in patients both with and without BRCA mutations [ 130 ].…”
Section: Promising Preclinical Studies Using Ovarian Cancer Organoids...mentioning
confidence: 99%
“…In another study using PDOs from a chemoresistant patient, treatment with AXL inhibitor AVB500 resulted in limited tumor survival when used in combination with olaparib, independently of the HR status of the tumor [ 130 ]. In addition, the inhibitor had a synergistic DNA-damaging effect with carboplatin and paclitaxel treatment, suggesting that AVB500 treatment could be beneficial in patients both with and without BRCA mutations [ 130 ]. In respect to DNA damage, the imminent PARP refractory poses an additional challenge, especially for the HR-deficient patients.…”
Section: Promising Preclinical Studies Using Ovarian Cancer Organoids...mentioning
confidence: 99%